STUDIES ON THE MODE OF IRON APPLICATION AND GROWTH REGULATORS ON THE PERFORMANCE OF DIRECT SEEDED UPLAND RICE (ORYZA SATIVA L.) VARIETIES UNDER RAINFED CONDITION - SARANGI, S.K.; SHARMA, H.C.; Singh, KALYAN; Singh, Y.; Singh, C.S.; SINGH, K.K. (Annals of Agricultural Research, 2014)
Field experiment was carried out to judge the mode of iron application and growth regulators on the performance of direct seeded upland rice varieties under rainfed condition at the Research Farm, Department of Agronomy, Institute of Agricultural Sciences, Banaras Hindu University, Varanasi, during rainy seasons of 2001 and 2002. Two varieties (ZHU-XI-26 and NDR-97) and three growth regulators (control, paclobutrazol and cycocel) were combined to give six main plot treatments whereas five subplot treatments were modes of iron application (control-M0), 25kg FeSO4 ha-1 as basal (M1), 1.0% foliar spray (10kg FeSO4 ha-1) and 1.5% (15kg FeSO4 ha-1) at 25 and 35 days after sowing (DAS), respectively (M2), 15 kg FeSO4 ha-1 based +1.0 10 h-1 foliar spray 15DAS (M1) and foliar spray of 0.1% Fe EDTA at 25 and 35 DAS (M4) were laid out in a split plot design with 3 replications. The available marked products of growth regulators paclobutrazol (cultar) and cycocel (lithocin) were applied @ 100ppm each at 20 and 40DAS through foliar spray. The variety ZHU-XI-26 performed better than NDR-97. Growth regulator paclobutrazol increased grain yield significantly over cycocel application. Among the mode of application, 15kg FeSO4 ha-1as based+ 1.0% (10 kg ha-1) foliar spray 35DAS though at par with foliar spray of 0.1% Fe EDTA at 25 and 35 DAS produced higher yield than other modes of application.